Tip-of-the-tongue Experiences. A Modest Proposal on Cognitive Phenomenology - Calabi, Clotilde (Phenomenology and Mind, 2017)
The experience of having a name on the tip of one’s tongue is often considered as evidence either in favor of pure cognitive phenomenology or against it. Yet the question of what kind of experience it is, is barely addressed. My task is to address this preliminary question. After discussing some answers to this question, I argue in favor of a pluralist account of TOTs, according to which they are second order beliefs about our knowledge of words, perceptions or bodily feelings.